1998
DOI: 10.1038/sj.bjp.0701802
|View full text |Cite
|
Sign up to set email alerts
|

Carbachol stimulation of gastric acid secretion and its effects on the parietal cell

Abstract: 1 The acid secretagogue eect of gastrin is mainly mediated by the release of enterochroman-like (ECL) cell histamine, but the mechanism of muscarinic stimulation of acid secretion remains unclear. The results of studying aminopyrine uptake in isolated parietal cells, and histamine release in isolated ECL cells suggest that muscarinic agents may act both directly on the parietal cell and indirectly via histamine release from ECL cells. 2 We examined parietal and ECL cell responses to the muscarinic agent carbam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Choline esters, such as acetylcholine and carbachol, have been claimed to mobilize histamine from rat and dog stomachs (Stubrin et al ., 1965; Sandvik et al ., 1988c; Gerber & Payne, 1992). On the other hand, there are reports demonstrating a lack of effect of choline esters on ECL‐cell histamine mobilization (Rosengren & Svensson, 1969; Sewing, 1969; Koyama et al ., 1987; Lindström et al ., 1997; Sandvik et al ., 1998; Lindström & Håkanson, 2001). In fact, in the present study, neither of the two choline esters stimulated histamine mobilization in vivo , nor did they inhibit gastrin‐stimulated histamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Choline esters, such as acetylcholine and carbachol, have been claimed to mobilize histamine from rat and dog stomachs (Stubrin et al ., 1965; Sandvik et al ., 1988c; Gerber & Payne, 1992). On the other hand, there are reports demonstrating a lack of effect of choline esters on ECL‐cell histamine mobilization (Rosengren & Svensson, 1969; Sewing, 1969; Koyama et al ., 1987; Lindström et al ., 1997; Sandvik et al ., 1998; Lindström & Håkanson, 2001). In fact, in the present study, neither of the two choline esters stimulated histamine mobilization in vivo , nor did they inhibit gastrin‐stimulated histamine release.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the cholinergic agent carbachol (Sandvik et al . ) nor electrical vagal stimulation (Norlen et al . ) releases histamine directly.…”
Section: Methods To Stimulate and Assess Gastric Acid Secretion And Pmentioning
confidence: 99%
“…In all cases, GAS is significantly reduced, indicating that there may be a significant depression in intracellular free Ca 2+ . It is generally accepted that gastrin acts mainly by releasing histamine from the enterochromaffin-like (ECL) cells in the oxyntic mucosa, so also from actions on parietal cells where they are equally distributed (Prinz, 1993(Prinz, , 1994aSandvik et al, 1998). Furthermore, it has been reported that prostaglandins do exert inhibitory effects on parietal cells (Soll, 1986).…”
Section: Resultsmentioning
confidence: 99%